Effect of an Aspergillus Meal Prebiotic on Salmonella Infection in Turkeys and Broiler Chickens - Londero, A.; Menconi, A.; Reginatto, A.R.; Bacocina, I.; Wolfenden, A.; Shivaramaiah, S.; Hargis, B.M.; Tellez , G. (International Journal of Poultry Science, 2011)
The objective of this study was to evaluate the effect of 0.2% dietary Aspergillus Meal (AM) against horizontal transmission of Salmonella sp. in turkeys and chickens. Experiment 1 evaluated the effect of AM against horizontal transmission of Salmonella Enteritidis (SE) in turkeys. Day-of-hatch turkeys were assigned to untreated control or AM prebiotic-fed groups. Five additional seeder turkeys per group were challenged with 1.5 x 105 cfu SE and placed in each of the treatment groups 24 h later. At ten, twenty and thirty days of age, Cecal Tonsils (CT) were cultured for SE recovery. A significant reduction in SE recovery (25%, 30% and 35% respectively) was observed in prebiotic-fed turkeys when compared with controls (p<0.05). In experiments 2 and 3, the effect of AM against horizontal transmission of Salmonella Typhimurium (ST) in chickens was evaluated. In each experiment, day-of-hatch chickens were assigned to untreated control or AM prebiotic-fed groups. Five additional seeder chicks per group were challenged with 1.25 x 105 cfu of ST and placed in each of the treatment groups 24 h later. At ten days of age, Liver/Spleen (L/S) and CT were cultured for ST recovery. In experiments 2 and 3, percent reduction of ST from L/S and CT were 60%, 75% and 55%, 60% respectively when compared to non-treated controls. These results suggest that the addition of AM as a prebiotic at 0.2% may have a beneficial effect in reducing Salmonella levels and may enhance overall food safety of poultry meat.